Authigenic uranium and stable isotopes of Globobulimina spp. and Cibicidoides wuellerstorfi from ODP Sites 202-1240 and 138-846 and excess barium fluxes from Site 202-1240 - Allison W Jacobel; Robert F Anderson; Samuel L Jaccard; Jerry F McManus; Frank J Pavia; Gisela Winckler (PANGAEA, 2019)
Authigenic uranium (aU), and stable isotope data of Globobulimina spp. and C. wuellerstorfi from ODP Sites 1240 and 846. Excess Barium (Baxs) fluxes from ODP 1240. Reconstructions of past changes in dissolved oxygen concentrations in the abyssal ocean are of interest to paleoceanographers because of their potential to help characterize and quantify the transfer of carbon between the atmosphere and the deep ocean. This potential, derived from the stoichiometric relationship between oxygen consumption and the regeneration of organic matter, has recently been expanded by compilations of core top observations for two proxies, the δ^1^3C gradient between coeval infaunal and epifaunal benthic foraminifera (Δδ^1^3C), and biomarker preservation. Here, we review these newer proxies, and the more established redox proxy authigenic uranium (aU), to critically evaluate our understanding of the controls on proxy production and preservation. We locate our work in the equatorial Pacific, presenting both new data and a compilation of existing records based on thirty-two sediment cores to draw semi-quantitative conclusions about bottom water oxygen and respired carbon concentrations over the last glacial period. We find that the biogeochemical limitations on these proxies may be more substantial than previously appreciated, and therefore suggest several best practice recommendations for their application. Despite the recognized data limitations, the compilation identifies the glacial Pacific Ocean as a dominant sink for CO? at all depths below the modern oxygen minimum zone. Our review emphasizes the importance of multiproxy reconstructions, informed by site-specific records of paleoproductivity, in drawing coherent, internally consistent conclusions about glacial ocean oxygenation and carbon storage.
Supplement to: Jacobel, AW et al. (2020): Deep Pacific storage of respired carbon during the last ice age: Perspectives from bottom water oxygen reconstructions. Quaternary Science Reviews, 230, 106065, https://doi.org/10.1016/j.quascirev.2019.106065